The Putative Thiosulfate Sulfurtransferases PspE and GlpE Contribute to Virulence of Salmonella Typhimurium in the Mouse Model of Systemic Disease - Wallrodt, Inke; Jelsbak, Lotte; Thorndahl, Lotte; Thomsen, Line E.; Lemire, Sebastien; Olsen, John E. (PLOS ONE, 2013)
The phage-shock protein PspE and GlpE of the glycerol 3-phosphate regulon of Salmonella enterica serovar Typhimurium are predicted to belong to the class of thiosulfate sulfurtransferases, enzymes that traffic sulfur between molecules. In the present study we demonstrated that the two genes contribute to S. Typhimurium virulence, as a glpE and pspE double deletion strain showed significantly decreased virulence in a mouse model of systemic infection. However, challenge of cultured epithelial cells and macrophages did not reveal any virulence-associated phenotypes. We hypothesized that their contribution to virulence could be in sulfur metabolism or by contributing to resistance to nitric oxide, oxidative stress, or cyanide detoxification. In vitro studies demonstrated that glpE but not pspE was important for resistance to H2O2. Since the double mutant, which was the one affected in virulence, was not affected in this assay, we concluded that resistance to oxidative stress and the virulence phenotype was most likely not linked. The two genes did not contribute to nitric oxid stress, to synthesis of essential sulfur containing amino acids, nor to detoxification of cyanide. Currently, the precise mechanism by which they contribute to virulence remains elusive.